Wernicke's encephalopathy mimicking neuropsychiatric symptoms in patients with systemic lupus erythematosus: a report of three cases and literature review. (February 2017) - Appenzeller, S; Reis, F; Costallat, L T Lavras; Pérez, J Adams; Saldanha, C F; Monticielo, O A
Systemic lupus erythematosus (SLE) is a chronic inflammatory disease that involves many organs and systems. Nervous system involvement in SLE encompasses neurological and psychiatric disorders, and remains a diagnostic and therapeutic challenge. Wernicke's encephalopathy (WE) is a neurological disorder that occurs as a consequence of thiamine deficiency, and its clinical presentation resembles the neuropsychiatric events attributed to SLE (NPSLE). Differentiation between these two entities is crucial because their treatment differs greatly and can change prognosis. We describe three cases of patients with SLE who presented with initial clinical findings suggestive of NPSLE that, at the end of a thorough clinical investigation, were actually found to represent WE. In all of these cases, treatment with thiamine resulted in significant improvement. WE should be considered as a differential diagnosis in SLE patients with neuropsychiatric signs and symptoms, especially when risk factors for thiamine deficiency are present.